MIS CONTRIBUTION DEGREE IN MAKING EDUCATIONAL DECISIONS FROM THE PERSPECTIVE OF THE EDUCATION PRINCIPLES OF IRBID DISTRICT - Maisoon Al-Zoubi (European Scientific Journal, ESJ, 2015)
This study aimed to reveal the degree of MIS contribution in making decisions from the perspective of principles. The study relied on the descriptive analytical method for the purpose of achieving its objectives. The study sample consisted of 221 employees of educational Irbid Districts (the first, the second, and the third). The study concluded that there is a statistically significant effect of MIS application degree at educational institutions in the Irbid District. It also shows the presence of a statistically significant effect of the degree of making educational decisions by the ministry of education principles at Irbid District. In addition, there is the presence of a statistically significant effect of the degree of making educational decisions at the education directorates in Irbid District. There is a presence of a statistically significant differences at the significance level (α ≤0.05) of the MIS contribution level in making educational decisions processes and instrument as a whole depending on the variable (sex, age, years of experience, educational qualification). The value (F) did not reach the level of statistically significant degree (α ≤0.05). The recommendations proposed to work on the introduction and integration of MIS in the supervision and rehabilitation of human resources process in the departments of Education.